The Impact of Supply Chain Management on Water Distribution: Literature Revie - Kuntoro, Bagus Dwi; Wahyudi, Muhammad Ilham; Andriawan, Didi (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to analyze the effect of Supply Chain Management (SCM) on the effectiveness of water distribution in a clean water provider company, in this case PT Air Minum Tabalong Bersinar (Perseroda) in the urban area of Tabalong Regency. In facing challenges such as distribution delays, water loss, and demand fluctuations, the implementation of SCM is considered to be able to improve efficiency and service. The study used a quantitative approach with a survey method of 130 respondents, consisting of employees and customers of PT Air Minum Tabalong Bersinar (Perseroda). The independent variables include raw water supply, inventory management, distribution, and information technology, while the dependent variable is the effectiveness of water distribution. Data analysis was carried out using multiple linear regression using SPSS version 25. The results showed that the four SCM variables simultaneously and partially had a significant effect on distribution effectiveness. The distribution component had a dominant influence, followed by inventory management and information technology. R² of 68.7% indicated that this analysis model could explain most of the variation in distribution effectiveness. These findings emphasize the importance of SCM integration, especially in distribution management and information systems, to improve timeliness, service quality, and customer satisfaction. This research provides practical contributions to management in designing more adaptive and efficient supply chain-based distribution strategies. Recommendations are directed at increasing the use of technology and strengthening relationships with stakeholders.